Wireless support system / Noor Ezri Mohamad Noor - Mohamad Noor, Noor Ezri (2005)
Wireless Technology is a new way of networking computers together without the limitations and costs of a wired network. This is a rapidly changing world that is the home turf of people who love technology. Nowadays wireless technologies become one of the most important in the network area. Mobile communications and GPS (Global Positioning System) technology has now evolved to the point where these technologies can be exploited to provide field user with up to date spatial information for any given location. This paper proposes an application that uses wireless communication to gather data. The application is called the Wireless Support System and designed to work as a position locator to track location. The user is able to know their location by download the maps using a mobile phone. The maps store at GPS TrackMaker database and should has a link vvdth GPRS server before it able to download on a mobile phone The system acknowledges the position data request and gathers these data from a Global Positioning System